2022
DOI: 10.1101/2022.07.25.501353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical modeling of plus-strand RNA virus replication to identify broad-spectrum antiviral treatment strategies

Abstract: Plus-strand RNA viruses are the largest group of viruses. Many are human pathogens that inflict a socio-economic burden. Interestingly, plus-strand RNA viruses share remarkable similarities in their replication. A hallmark of plus-strand RNA viruses is the remodeling of intracellular membranes to establish replication organelles (so-called “replication factories”), which provide a protected environment for the replicase complex, consisting of the viral genome and proteins necessary for viral RNA synthesis. In … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 133 publications
(207 reference statements)
0
1
0
Order By: Relevance
“…Zitzmann et al have used a version of the same model to analyse the effects of exosomal and viral RNA secretion in HCV [117], as well as to study the within-cell dynamics of dengue virus replication, with account for host immune responses [116]. Very recently, Zitzmann et al [118] considered a generic model of intracellular viral replication and showed that with very minor virus-specific changes, the model could be fit quite well to the measurements of viral replication of HCV, DENV and Coxsackie virus B3 (CVB3). This model has provided important insights into shutting down mRNA translation in host cells being a vital factor in controlling the efficiency of viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…Zitzmann et al have used a version of the same model to analyse the effects of exosomal and viral RNA secretion in HCV [117], as well as to study the within-cell dynamics of dengue virus replication, with account for host immune responses [116]. Very recently, Zitzmann et al [118] considered a generic model of intracellular viral replication and showed that with very minor virus-specific changes, the model could be fit quite well to the measurements of viral replication of HCV, DENV and Coxsackie virus B3 (CVB3). This model has provided important insights into shutting down mRNA translation in host cells being a vital factor in controlling the efficiency of viral replication.…”
Section: Introductionmentioning
confidence: 99%